Particle image velocimetry studies of an oscillating flow in a thermoacoustic device - Saad, Michael Rezk (AUC Knowledge Fountain, 2013)
Flow visualization is a necessity in thermoacoustic devices to study the behavior of the devices and relate visualization outcomes to other experimental and computational results to help obtaining a complete understanding of physics of flow in thermoacoustics. In this work particle image velocimetry (PIV) was used to investigate the effects of changing the porosity and length of meshed ceramic stacks on the acoustic behavior of thermoacoustic oscillations in a thermoacoustic refrigerator with no heat exchangers and operated at atmospheric pressure. PIV was also used to study the vortex generation morphology at the premises of parallel plate stacks as vortices are one important source of efficiency loss in thermoacoustic devices. A glass-quartz acoustic resonator was built with a loudspeaker attached to induce a standing acoustic wave inside the resonator. Meshed ceramic stacks with different porosities and lengths were utilized to study the acoustic behavior. In addition, sets of parallel plates of aluminum and acrylic were used to study the flow morphology. The acoustic behavior measurements showed that as the meshed stack porosity increases the value of the acoustic power decreases unlike expected. This concludes that the viscous friction effects are dominant over the change in porosity as far as the gas parcel velocity and acoustic pressure amplitude are concerned. The morphology study aimed at visualizing the change in vortex generation behavior at different amplitudes and different configurations of the parallel plate sets. The results showed that as the amplitude of the dynamic pressure increases the size and displacement of a vortex increases. Also, as the plate spacing decreases the amount of disturbance increases due to the interaction of vortex structures together. Additionally, the combined effect of increasing amplitude and decreasing plate spacing would lead to higher disturbance. Vortex shedding was not observed, but visual inspection of the results showed that the existence of vortex shedding is affected by both the frequency and the dynamic pressure. Vortex shedding would occur if the acoustic cycle period is less than the time required by a vortex to completely develop. The time of vortex development is a function of its size and thus of the dynamic pressure amplitude. The results also showed that the flow in between the parallel plates is disturbed only when a vortex re-enters into the parallel plate channels. The amount of disturbance that the re-entering vortex causes is directly proportional to the size of the vortex.